Association Between Preoperative Blood Glucose Level and Hospital Length of Stay for Patients Undergoing Appendectomy or Laparoscopic Cholecystectomy - Hsiu‐Yin Chiang; Kuan-Ting Lin; Ya‐Luan Hsiao; Han-Chun Huang; Shih‐Ni Chang; Chien-Hui Hung; Ying Chang; Yu-Chun Wang; Chin‐Chi Kuo (2020)
To evaluate the effect of preoperative blood glucose (POBG) level on hospital length of stay (LOS) in patients undergoing appendectomy or laparoscopic cholecystectomy.We conducted a retrospective cohort study of patients aged ≥18 years who had undergone appendectomy or laparoscopic cholecystectomy procedures between 2005 and 2016 at a tertiary medical center in Taiwan. The association between POBG level and LOS was evaluated using a multivariable quasi-Poisson regression with robust variance. Multiple imputations were performed to replace missing values.We included 8,291 patients; 4,025 patients underwent appendectomy (appendectomy group) and 4,266 underwent laparoscopic cholecystectomy (laparoscopic cholecystectomy group). In the appendectomy group, patients with POBG levels of ≥123 mg/dL (adjusted relative risk [aRR] 1.19; 95% CI 1.06-1.33) had a 19% higher risk of having a LOS of >3 days than did those with POBG levels of <106 mg/dL. In the laparoscopic cholecystectomy group, patients with POBG levels of ≥128 mg/dL also had a significantly higher risk of having a LOS of >3 days (aRR 1.17; 95% CI 1.07-1.29) than did those with POBG levels of <102 mg/dL. A positive dose-response curve between POBG and an adjusted risk of a LOS of >3 days was observed, although the curve starts to flatten at a POBG level of ∼130 mg/dL.We demonstrated that a higher POBG level was significantly associated with a prolonged LOS for patients undergoing appendectomy or laparoscopic cholecystectomy. The optimal POBG level may be lower than that commonly perceived.